Advantages and disadvantages of renewable energy: a review of the scientific literature - Freires, Francisco Júnior (2023)
Civilizations are large energy consumers, so the more civilized a people, the greater their energy consumption. However, studies have shown that the way energy is produced is polluting and focused on finite resources. This study aimed to take stock of the scientific literature on renewable energies, identifying their advantages and disadvantages. The conceptual bibliographic method was used in its four stages: formulation of guiding questions, collection and organization of data, and presentation of responses generated by handling data obtained from Google Scholar and Periódico Capes. The results showed that a) renewable energy comes from a natural cyclothymic source, b) the advantages of renewable energy are almost all of an environmental nature, and c) the disadvantages are of an economic-financial nature. The conclusion shows that the time has come for a decision to be made between paying the high price of environmental sustainability or continuing with the lower costs of compromising the continuity of life on the planet.